An Iron Shield to Protect Epigallocatehin-3-Gallate from Degradation: Multifunctional Self-Assembled Iron Oxide Nanocarrier Enhances Protein Kinase CK2 Intracellular Targeting and Inhibition - Luca Fasolato; Massimiliano Magro; Giorgio Cozza; Ferruccio Sbarra; Simone Molinari; Enrico Novelli; Fabio Vianello; Andrea Venerando (MDPI AG, 2021)
Protein kinase CK2 is largely involved in cell proliferation and apoptosis and is generally recognized as an Achilles' heel of cancer, being overexpressed in several malignancies. The beneficial effects of (−)-epigallocatechin-3-gallate (EGCG) in the prevention and treatment of several diseases, including cancer, have been widely reported. However, poor stability and limited bioavailability hinder the development of EGCG as an effective therapeutic agent. The combination of innovative nanomaterials and bioactive compounds into nanoparticle-based systems demonstrates the synergistic advantages of nanocomplexes as compared to the individual components. In the present study, we developed a self-assembled core-shell nanohybrid (SAMN@EGCG) combining EGCG and intrinsic dual-signal iron oxide nanoparticles (Surface Active Maghemite Nanoparticles). Interestingly, nano-immobilization on SAMNs protects EGCG from degradation, preventing its auto-oxidation. Most importantly, the nanohybrid was able to successfully deliver EGCG into cancer cells, displaying impressive protein kinase CK2 inhibition comparable to that obtained with the most specific CK2 inhibitor, CX-4945 (5.5 vs. 3 µM), thus promoting the phytochemical exploitation as a valuable alternative for cancer therapy. Finally, to assess the advantages offered by nano-immobilization, we tested SAMN@EGCG against Pseudomonas aeruginosa, a Gram-negative bacterium involved in severe lung infections. An improved antimicrobial effect with a drastic drop of MIC from 500 to 32.7 μM was shown.